Pengaruh Harga, Citra Merek, dan Kualitas Produk terhadap Loyalitas Pelanggan Gula Pasir Gulaku (Survey Pada Konsumen DM Swalayan Yogyakarta) - Ardhianto Karsa Sunaryono, Ramadhani; Adhi Saputro, Wahyu; Sulistyowati, Ecclisia (Universitas Duta Bangsa Surakarta, 2025)
One of the staples for people's consumption is sugar. Sugar is used as a source of calories and functions as a sweetener. Until now sugar has not been replaced as the main sweetener. The purpose of this study was to determine the effect of price, brand image and product quality on customer loyalty